A comparative study of mineral contents in selected Malaysian brown rice and white rice / Bagirathy a/p Govarethinam - Govarethinam, Bagirathy (2014)
In the present study, concentration of minerals Na, Mg, K, Ca, Mn, Fe, Cu and Zn in selected commercially available brown rice and white rice from Malaysia were determined using microwave assisted digestion with inductively coupled plasma mass spectrometry. The data obtained were evaluated using chemometric tools. Hierarchical cluster analysis and principal component analysis visually reveal the natural clustering of rice sample into two distinct clusters where brown rice are associated with higher mineral concentration. The statistics show that all the mineral concentrations found in brown rice are significantly higher than those found in white rice (P<0.001). As a whole, the mean concentration of minerals follow a trend of K>Mg>Zn>Mn>Ca>Fe>Na>Cu for brown rice samples and a trend of K>Mg>Zn>Ca>Mn>Fe>Na>Cu in white rice samples.